2014
DOI: 10.1177/0031721714553412
|View full text |Cite
|
Sign up to set email alerts
|

The phantom collapse of student achievement in New York

Abstract: When New York state released the first results of the exams under the Common Core State Standards, many wrongly believed that the results showed dramatic declines in student achievement. A closer look at the results showed that student achievement may have increased. Another lesson from the exams is that states need to closely coordinate new data with existing data when they switch to different measuring instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, APPR was not the only major reform implemented during this time period. Many schools also were implementing the Common Core standards; the implementation of these standards coincided with the release of new state assessments with higher cut scores, which were intended to challenge students and teachers to attain higher levels of performance (Cronin & Jensen, 2014). Further, this policy was implemented amid an economic recession, which contributed to a 4% decline in the number of teachers (about 8,000) employed in the state before the study period began (Associated Press, 2011), with some teachers rehired as the policy was being implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, APPR was not the only major reform implemented during this time period. Many schools also were implementing the Common Core standards; the implementation of these standards coincided with the release of new state assessments with higher cut scores, which were intended to challenge students and teachers to attain higher levels of performance (Cronin & Jensen, 2014). Further, this policy was implemented amid an economic recession, which contributed to a 4% decline in the number of teachers (about 8,000) employed in the state before the study period began (Associated Press, 2011), with some teachers rehired as the policy was being implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Let’s concede that it is challenging because APPR was not implemented in a laboratory-like environment. APPR’s launch program coincided with the state’s introduction of Common Core standards, the adoption of new state assessments in support of those standards, and increased cut scores on state assessments that reflected college- and career-ready expectations for students (Cronin & Jensen, 2014). Further, the program was launched during an economic decline in which teachers and administrators were being laid off in the wake of the 2007 recession.…”
mentioning
confidence: 99%
“…Recent analysis of the bilingual education controversy indicated that linguistic minority children in the public school system are optimally educated through an early intervention of bilingual education, for it has been argued that bilingual education appears to overcome language and educational barriers (Padilla et al, 1991). Notwithstanding the contrary arguments of ineffectiveness of bilingual education, several innovative bilingual programs have shown that students enrolled in those programs showed significantly increased academic achievement (e.g., Baca & Amato, 1989;Cummings, 1986;Kerman, 1979). Mercer, an advocate of the educational rights of minority students and a strong critic of standardized IQ tests since the early 1970s (1972), developed the System of Multicultural Pluralistic Assessment (SOMPA) in order to assess the intelligence of low socioeconomic status (SES) minority children in a nonbiased manner (Mercer & Lewis, 1977).…”
Section: Overcoming Test Biasmentioning
confidence: 99%
“…AYP identifies the minimum percentage of students required to score at or above the designated cut-off score in English Language Arts and mathematics in order for schools to meet AYP [5,17]. Students who do not meet the cut score requirement are often placed in Summer Academy to improve their content acquisition, attain proficiency, and avoid grade retention [18].…”
Section: Introductionmentioning
confidence: 99%